The Impact of Performance Reporting Pressure and Information Asymmetry on Earnings Quality - Bintang Alexander Hermawan Bintang; Eric Hermawan; Sri Hastutik; Rudianto Hermawan; Dipa Teruna Awaludin (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Earnings quality serves as a crucial indicator of the credibility of financial reporting, significantly influencing investors' decision-making, corporate valuation, and capital market efficiency. Nevertheless, the escalating pressure to meet financial performance targets, coupled with persistent information asymmetry between managers and external stakeholders, may undermine the reliability of reported earnings. This study aims to investigate the effects of performance reporting pressure and information asymmetry on earnings quality among companies listed on the Indonesia Stock Exchange (IDX). Grounded in Agency Theory and Signaling Theory, the research employs a quantitative explanatory design utilizing secondary data sourced from audited annual reports and financial statements. The sample comprises non-financial firms selected through purposive sampling during the observation period from 2021 to 2025. Panel data regression analysis is utilized to evaluate the proposed hypotheses following the necessary diagnostic and model selection tests. This research is anticipated to provide empirical evidence regarding the extent to which organizational reporting pressure and information asymmetry affect the quality of corporate earnings in an emerging market context. The findings are expected to enrich the accounting literature by enhancing the understanding of earnings quality determinants and offering practical implications for regulators, investors, auditors, and corporate managers in improving financial reporting transparency and mitigating opportunistic reporting behavior.